(3eHOC MQjI GdefGaSI aj GdYbhO GdEOGQjI GdOhdj`I (B: s (3OQGSI JWHjbjI ebGQfI Ydi YbhO GdebGhdGJ GdOhdjI (B/ s - (3eUWai EHQGgje eUWai eMeO YHjOs; (3LGHQ LGO fUGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2018)
(3JfGhdJ GdQSGdI aUd JegjOi Yf eHOC MQjI GdefGaSI ai GdYbhO GdEOGQjI GdOhdjI(B: (3GdebUhO HeHOC MQjI GdefGaSI ai GdYbhO GdEOGQjI GdOhdjI h OQGSI GdfXGe GdbGfhfi dfXGe GdefGaSI(B: (3Ke beJ HJbSje GdHMK dbSejf(B: (3GdbSe GdChd GdEWGQ GdJfXjei deHOC MQjI GdefGaSI ai GdYbhO GdEOGQjI GdOhdjI h Pdc ai HGHjf JfGhdJ ai GdChd efgG YQV GdEWGQ GdbGfhfi deHOC MQjI GdefGaSI ai GdYbhO GdEOGQjI GdOhdjI(B. (3h ai GdHGH GdKGfi JfGhdJ OQGSI GdbjhO GdhGQOI Ydi eHOC MQjI GdefGaSI ai GdYbhO GdEOGQjI GdOhdjI(B. (3GdbSe GdKGfi(B: (3ef GdHMK JfGhdJ ajg OQGSI JShjI GdefGRYGJ GdeJYdbI HeHOC MQjI GdefGaSI h Pdc ai HGHjf GdChd efgG JShjI GdefGRYGJ GdeJYdbI HeHOC MQjI GdefGaSI ai GdCfXeI GdOGNdjI(B. (3h GdHGH GdKGfi JfGhdJ ajg fXe JShjI GdefGRYGJ GdOhdjI GdeJYdbI HeHOC MQjI GdefGaSI h WQb GeJjGR fXGe GdJMcje HEYJHGQg EMOi GdWQb GdHOjdI Yf GddLhA ddbVGA(B: (3h fJGFL GdHMK h JhUjGJg Ke NGJeI GdHMK h GdeQGLYs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2018. s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdEOGQjs; (3eHOC MQjI GdefGaSIs; (3GdYbhO GdEOGQjI GdOhdjIs; (3GdeYhbGJ GdbGfhfjIs; (3YbhO GdebGhdGJ GdOhdjIs; (3JShjI GdefGRYGJ GdOhdjIs; (3GdJMcje aj GdYbhO GdEOGQjIs; (3GdbGfhf GdaQfSjs; (3GdbGfhf GdchjJjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2018